Divided Government and Polarization: Regression-Discontinuity Evidence from US States - Luca Repetto; Maximiliano Andrés Sosa (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper studies how divided government – arising when control of the government branches is split between parties – affects the polarization of the legislature and policy implementation. Using data on electoral and legislative outcomes for US states and a regression-discontinuity design, we show that Republican state senators are substantially more polarized when they serve in a divided government than they are in a fully unified government. We find similar but smaller effects for Democrats. In addition, governors facing an opposing, united legislature veto more bills, and have more of these overridden. However, in terms of policy implementation, we find evidence of moderation: when a unified Republican government loses a chamber or the governor to the Democratic party, the implemented legislation becomes much more liberal. Correspondingly, when Democrats lose unified control, policies become more conservative. These results suggest that divided government creates incentives for legislators to polarize knowing they will need to compromise in order to obtain their preferred policy.
Keywords: H10; H70; R50; 330; divided governments; polarization; policy liberalism; regression-discontinuity design; US state governments